The Quaternary vertebrate fauna of cave deposits of the Podillia-Bukovynian Karst-Speleological Area (Western Ukraine). - Ridush, Bogdan (Stratigraphy & Timescales, Elsevier, 2022)
The Podillia-Bukovinian Karst-Speleological Area is rich in numerous caves of karst, suffosion, and weathering origin. The gypsum karst is the most widespread here. It is famous for the largest in the World maze-caves in gypsum. Some of these caves contain Quaternary sediments with vertebrate fauna that can be used for biostratigraphy. The first faunal remains were found as early as 1886. Now here, there are known at list 30 cave sites with the Quaternary vertebrate fauna. Most of the sites are in horizontal caves, which results in specific bones and sediment accumulation. The formation of most of the bone accumulations is related to the inhabiting of caves by the troglophilic species, especially carnivores, and only a few with inhabiting by humans. The oldest among the cave sites is Chortkiv, dated to the late Odesian Fauna (Kryzhanivka Stage, MIS 41-62). The best-studied cave sections with cave fauna are Bukovynka, Kryshtaleva (Kryvchanska), Pryima I, Chortovi Skeli (Lviv VIII). Several caves are promising for further research, such as Martynivka, Tovtry, and others. A very small part of the osteological material was published in detail. Only 15 radiocarbon data are known for the cave sites in the region. Many finds in caves were made in the 1950s-1960s, sometimes occasionally. Part of the bone collections was lost. The material stored in museums should be revised. The are still has a large potential for the future research of the Quaternary cave deposits.
Keywords: Quaternary; cave deposits; karst; Podillia-Bukovynian karst area; mammalian fauna